Developing a Low-Cost Safety Improvement Program for Intersections in an Urban Roadway Network: A Case Study - Promothes Saha (Advances in Civil Engineering)
In the US, about 40% of all crashes involve intersections. As improving safety at intersections and nonintersections are significantly different, it is important to manage them separately within a limited budget. In this study, a safety improvement program was developed for intersections and implemented in the city of Fort Wayne, Indiana, as a case study. Intersections included in the safety improvement program were selected using the following criteria and constraints: averaging more than 3 crashes per year during the study period, crash rate, and fatal and injury crash rate, limited budget, and safety benefits. Selected intersections were analyzed to characterize their crashes by type and frequency. Countermeasures were proposed and analyzed to address those crash types identified in the crash characterization. Linear integer optimization technique was employed to identify the best set of countermeasures within a limited budget. A safety improvement program was proposed based on this analysis that would cost $81,232 and provide a 5-year crash reduction benefit of more than $15 million preventing approximately 164 total crashes and 61 fatal or injury crashes.